THE ROLE OF THE STATE IN INSTITUTIONAL ECONOMICS THEORY (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This article provides a scientific and theoretical analysis of the place and role of the state within the framework of institutional economics theory. The impact of institutions, formal and informal rules on economic development is examined. The functions of the state in shaping legal, economic, and social institutions, as well as its importance in ensuring economic stability and efficiency, are substantiated. In addition, the practical significance of institutional reforms for developing countries is highlighted.